UJI KLINIK MULTISENTER PENGARUH FORMULA JAMU OSTEOARTHRITIS TERHADAP RASA NYERI DIBANDING PIROXICAM - Danang Ardiyanto; Peristiwan R Widhi Astana (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Herb scientification program is expected to obtain scientific evidence of the use of herb through research-based services. The purpose of this study is to reveal the efficacy of pain relief herb for osteoarthritis (OA) compared to the standard drug piroxicam. This clinical study performed through multi-center clinical trial approach involving 30 physicians who have been trained in herbs scientification trainee in February to December 2014. The study design was an open clinical trial without blinding. 123 patients with OA who met the inclusion criteria included in this study and they divided into two groups (63 subjects treat with OA herb and 60 subjects treated with piroxicam (as a control group). The OA herb consists (Curcuma xanthorrhiza roxb rhizome (15 g), Phyllanthus urinaria herbs (7 g), Curcuma domesticae rhizoma (15 g), Foeniculum vulgare Mill seeds (3 g), Orthosiphon aristatus leaves (5 g), and Acalyptha india herb (5 g)). Data collected for four weeks in both groups of patients. This clinical study concludes that the treatment of OA herb for 28 days significantly decrease the pain in patients with osteoarthritis. OA herbs can reduce the patient's VAS scores were comparable to piroxicam (p> 0.05). Key words: Osteoarthritis, pain relief herb, VAS, piroxicam